International Finance in Emerging Markets Issues, Welfare Economics Analyses and Policy Implications - Hansanti, Songporn; Islam, Sardar M. N.; Sheehan, Peter; SpringerLink (Online service) (Heidelberg : Physica-Verlag HD : Imprint: Physica, 2008)
The book "International Finance in Emerging Markets" reviews contemporary issues in international monetary and financial economics in an emerging financial market using the example of Thailand. The book adopts the elements of new welfare economics and asymmetric information paradigms in analyzing those issues including financial liberalization, crisis, exchange rate determination, and domestic capital market reform. The book suggests for the first time a normative social approach for addressing the contemporary issues in international monetary and financial economics. It provides an example of cutting edge research in international finance and monetary economics within a welfare economics framework. It also suggests some policy implications of the welfare economic analysis of international financial issues in an emerging market. "This new book suggests a normative social approach for addressing international monetary and financial economic issues. To this end, the novelty of the book is to make use of new welfare economics and asymmetric information paradigms in analyzing the international financial issues in Thailand. Surely this book will soon become an important reference book by researchers, academics, professionals and postgraduate students in the areas of finance, financial economics and monetary economics." Dr. Bruno S. Sergi, Professor of International Economics, University of Messina, Italy " This book addresses contemporary issues in international monetary policy and finance from a welfare economics perspective, focusing on emerging market nations such as Thailand. It is a welcome contribution to the international finance literature." Prof. Steven L. Schwarcz, Stanley A. Star Professor of Law & Business, and Founding Director, Global Capital Markets Center, Duke University, USA .
Literature Review – The Emerging Issues -- Recent Issues in International Finance: A Literature Review -- Overview of Thailand’s Approach to Financial Liberalisation -- The Thai Experience -- Analysis of Sequencing of Financial Liberalisation in Thailand -- Capital Controls: Consequences of Financial Liberalisation -- Exchange Rate Policy and Its Consequences -- Welfare Economies, Economic Theory and Policy -- Review of Financial Liberalisation Theory and the Thai Crisis -- A Cost and Benefit Analysis Model for Globalisation: Some Social Welfare Implications of Thailand’s Globalisation Process -- Conclusions and Policy Implications.
Keywords: Macroeconomics; Development economics; Macroeconomics/Monetary Economics//Financial Economics; Development Economics